The Use of High-Density Pedicle Screw Construct with Direct Vertebral Derotation of the Lowest Instrumented Vertebra in Selective Thoracic Fusion for Adolescent Idiopathic Scoliosis: Comparison of Two Surgical Strategies - Chang, Sam Yeol; Kim, Jae Hun; Mok, Sujung; Chang, Bong-Soon; Lee, Choon-Ki; Kim, Hyoungmin (Asian spine journal, 2023)
Study Design: This study was a retrospective case series.Purpose: This study was designed to determine whether direct vertebral rotation (DVR) of the lowest instrumented vertebra (LIV) using a high-density (HD) construct can reduce fusion segments without increasing adverse outcomes in selective thoracic fusion (STF) for adolescent idiopathic scoliosis (AIS).Overview of Literature: LIV DVR is used to maximize spontaneous lumbar curve correction and reduce adverse outcomes during STF for AIS. However, evidence is limited on whether LIV DVR can allow a proximally located LIV and reduce fusion segments without increasing adverse outcomes.Methods: We reviewed consecutive patients with Lenke 1 AIS who underwent STF from 2000 to 2017. The patients were divided into two groups based on the surgical strategy used: low-density (LD) construct without DVR of the LIV (LD group) versus HD construct with DVR of the LIV (HD group). We collected data on the patient’s demographic characteristics, skeletal maturity, operative data, and measured radiological parameters in the preoperative and final follow-up radiographs. The occurrence of adding-on (AO) and coronal decompensation was also determined.Results: In this study, 72 patients (five males and 67 females) with a mean age of 14.1±2.3 years were included. No significant differences in the demographics, skeletal maturity, and Lenke type distribution were observed between the two groups; however, the follow-up duration was significantly longer in the LD group (64.3±25.7 months vs. 40.7±22.2 months, p <0.001). The HD group had significantly shorter fusion segments (7.1±1.3 vs. 8.5±1.2, p <0.001) and a more proximal LIV level (12.1±0.9 vs. 12.7±1.0, p =0.009). In the radiological measurements, the improvement of LIV+1 rotation (Nash–Moe scale) was significantly larger in the HD group (0.53±0.51 vs. 0.21±0.41, p =0.008). AO and decompensation occurred in 7 (9.7%) and 4 (5.6%) patients in the HD and LD groups, respectively, without any significant difference between the two groups.Conclusions: In this study, the HD group had a significantly shorter fusion level and a more proximal LIV than the LD group; however, the two groups had similar curve correction and adverse radiological outcome rates.